Eskalasi Kemampuan Berpikir Kritis Mahasiswa Psikologi Universitas Jambi Melalui Kegiatan Interaktif Psikoedukasi - Nurul Hafizah; Desiana Misgi Suryani; Putri Zahra Aisyah; Wulan Pratiwi; Aulia Azzahra Ibrahim; Endrina Juwita Zahra; Fatia Risya Nursyifa; Muhammad Ravi Diponegoro; Muhammad Asif Rasyhad (Prima Abdika: Jurnal Pengabdian Masyarakat, 2026)
This community service program aims to improve the critical thinking skills of Psychology students at the University of Jambi through interactive psychoeducational activities. The background of this community service is the low critical thinking skills of students, as demonstrated by a tendency to accept information without in-depth analysis and minimal active participation in the learning process. The implementation method is a three-day psychoeducational program conducted at the Jambi Agricultural Training Center, involving Psychology students from the 2024–2025 intake. The activity stages include collecting initial data through questionnaires, Focus Group Discussions, and interviews, followed by implementing psychoeducation based on CEK-IN (Cermati dan Kritisi Informasi) materials, SIGAP case study discussions, and the interactive Tower of Logic game. The activity evaluation was carried out using pretest and posttest methods to measure changes in participants' logical reasoning abilities. The results showed that most participants experienced increased and stable critical thinking skills after participating in the psychoeducational activities, while a decrease in scores among a small number of participants was attributable to situational factors. These findings indicate that interactive psychoeducation is effective in developing students' critical thinking skills and can serve as an alternative learning strategy that encourages analytical, reflective, and logical attitudes when facing academic and daily-life challenges.